The Influence of Overconfidence and Investment Motivation on Investment Decisions of UMKM Actors in Kediri City Through Investment Interest as An Intervening Variable - Sari, Okta Viana Sri Pratama; Buniarto, Edwin Agus; Saptaria, Lina (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the influence of overconfidence and investment motivation on investment decisions of MSMEs in Kediri City through investment interest as an intervening variable. The population in this study were MSMEs in Kediri City. This study used a purposive sampling method to determine the sample size, which was 100 samples. Data came from questionnaires filled out by MSMEs in Kediri City. The data analysis method used was the Partial Least Square (PLS) method. The results of this study indicate a positive and significant influence between the investment interest variable on investment decisions, but no significant influence was found between investment motivation and overconfidence on investment decisions. On the other hand, there was a positive and significant influence between the investment motivation and overconfidence variables on investment interest. In other words, the investment interest variable can strengthen and weaken the influence of investment motivation and overconfidence on investment decisions of MSMEs in Kediri City.